A combined biomechanical analysis of the flip turn technique - Pereira, S.; Vilar, S.; Goncalves, P.; Figueiredo, P.; Fernandes, R.; Roesler, H.; Vilas-Boas, J. P. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to biomechanically describe the front crawl flip turn technique of an elite male swimmer using and integrating dynamometric, kinematical and electromyographic (EMG) data. Surface active bipolar electrodes, two underwater and four surface fixed cameras, and an underwater force plate were used to evaluate the several phases of this turn. It was observed that the turn rotation phase was performed very close to the wall, imposing excessive lower limb joint flexions, and determining a too long contact phase. Those findings presented probable consequences upon the force curve, the pattern of muscular recruitment, and the velocity of the take-off the wall. However the trunk angle at the take-off the wall allowed a good position during the impulse phase. Therefore, this high level swimmer should improve these aspects in order to improve his performance.